An Analysis on Determinants of Energy Intensity in ASEAN Countries - Fajar Fitriyanto; Deden Dinar Iskandar (Jurnal Ekonomi dan Studi Pembangunan, 2019)
ASEAN is a region with a high level of economic growth. However, ASEAN region is also faced with several important issues in the energy sector such as high energy consumption growth, fossil energy dependency, and fluctuations in energy prices. Energy efficiency is viewed as the proper way to enhance energy security. The concept of energy intensity (ratio of energy consumption per GDP) is used to describe the level of energy efficiency. The objective of the research is to analyze factors that influence energy intensity in ASEAN region. This study uses secondary data in the nine Southeast Asian countries in 2001-2014. This study employs an analysis with Arellano Bond Generalized Method of Moments (GMM) panel data to analyze factors that affect energy intensity. The results of the study find that the variable of GDP per capita and energy prices have a significantly negative effect on energy intensity. The variable of energy consumption per capita has significantly positive effect on energy intensity. The variables of trade openness and foreign direct investment have no significant effect on energy intensity